2011
DOI: 10.1103/physrevlett.107.075503
|View full text |Cite
|
Sign up to set email alerts
|

Observation of a Martensitic Structural Distortion in V, Nb, and Ta

Abstract: Thermal-expansion measurements of the Group 5 elements V, Nb, and Ta reveal a structural distortion below 300 K. Data for single-crystalline Nb and Ta display anisotropic thermal expansion, martensitic in character, that is inconsistent with cubic crystal structures at low temperature. Published results on V show similar behavior. Interstitial impurities suppress the transition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 24 publications
2
21
0
1
Order By: Relevance
“…[1][2][3][4][5] Short-range order and superconductivity of V-Nb, V-Ta, and Nb-Ta alloys have been examined for understanding the influence of alloying on the superconducting transition temperatures. 2 Recently, V, Nb, and Ta have been found to undergo a martensitic-like structural distortion [3][4][5] in which they transform from the high-temperature bcc structure to either a rhombohedral structure or to a tetragonal structure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5] Short-range order and superconductivity of V-Nb, V-Ta, and Nb-Ta alloys have been examined for understanding the influence of alloying on the superconducting transition temperatures. 2 Recently, V, Nb, and Ta have been found to undergo a martensitic-like structural distortion [3][4][5] in which they transform from the high-temperature bcc structure to either a rhombohedral structure or to a tetragonal structure.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] Short-range order and superconductivity of V-Nb, V-Ta, and Nb-Ta alloys have been examined for understanding the influence of alloying on the superconducting transition temperatures. 2 Recently, V, Nb, and Ta have been found to undergo a martensitic-like structural distortion [3][4][5] in which they transform from the high-temperature bcc structure to either a rhombohedral structure or to a tetragonal structure. Apart from this, vanadium-based alloys are known to have the desired combination of physicomechanical properties, compatibility with nuclear fuel, and high resistance to corrosion 6,7 making them potential structural materials for fast-neutron nuclear power plants which can be operated at temperatures exceeding 1000 K for increasing the thermodynamic efficiency of electric power production.…”
Section: Introductionmentioning
confidence: 99%
“…Anisotropy could develop below T N after the subtle tetragonal distortion of the cubic crystal structure of α-Mn occurs. Such thermal expansion anisotropy was recently reported for temperatures below Martensitic structural distortions in single crystals of Nb and Ta [33]. However, it might be challenging to resolve any thermal-expansion anisotropy in α-Mn if it were masked by the effects of twinning or the formation of structural domains.…”
Section: Introductionmentioning
confidence: 94%
“…the stability of the cubic phase was evaluated and found to be consistently stable, regardless of the degree of disorder) and an experimental statement. While it was speculated that the martensitic transformation does occur in bcc Nb by Bollinger et al [195], a subsequent evaluation of the temperature dependent lattice parameters by Francoual et al [196] showed that this prediction is not correct.…”
Section: Introductionmentioning
confidence: 99%